Mantle cell lymphoma with EBV‐positive Hodgkin and Reed–Sternberg‐like cells in a patient after autologous PBSCT: Phenotypically distinct but genetically related tumors. Issue 1 (20th October 2020) - Kanai, Risa; Miyagawa‐Hayashino, Aya; Shishido‐Hara, Yukiko; Nakamura, Naoya; Omatsu, Ikoi; Morinaga, Yukiko; Shimura, Yuji; Kuroda, Junya; Imura, Tetsuya; Itoh, Kyoko; Konishi, Eiichi
Abstract : The case of 70‐year‐old man with mantle cell lymphoma (MCL) carrying t(11;14) translocation that relapsed as nodal lymphoma combining MCL and classic Hodgkin lymphoma (cHL) 9 years after autologous peripheral blood stem cell transplant (auto‐PBSCT) is reported. Lymph nodes contained two separate areas of MCL and cHL‐like components. Hodgkin and Reed–Sternberg (HRS)‐like cells were accompanied by a prominent histiocyte background. HRS‐like cells were CD5 −, CD15 +, CD20 −, CD30 +, PAX5 +, Bob.1 −, Oct2 − and EBER + . The MCL component expressed cyclin D1 and SOX11, whereas cyclin D1 and SOX11 expressions were reduced and lost, respectively, in HRS‐like cells. Polymerase chain reaction results showed a single clonal rearrangement of the IGH gene in MCL and cHL‐like components. CCND1 break apart fluorescence in situ hybridization showed split signals in both MCL and HRS‐like cells, suggesting that MCL and cHL‐like components were clonally related. Acquisition of p53 expression and Epstein–Barr virus (EBV)‐positivity was seen in HRS‐like cells. The patient died of disease progression with elevated hepatobiliary enzymes. The autopsy showed both MCL and cHL‐like components around the bile ducts, splenic white pulp and bone marrow. The two components were phenotypically distinct, but genetically related, suggesting that transformation of MCL to HRS‐like cells during the course of MCL in association with EBV infection.